ANALISIS POTENSIAL BAHAYA DAN RISIKO KECELAKAAN KERJA DENGAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS - Kaidah, Sri; Prasojo, Wahyu Hari; Prasetio, Muhammad Ari; Sitorus, Tosty Maylangi (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2024)
Every workplace has a risk of occupational accidents. A work accident is an unplanned and uncontrollable event caused by human factors, the Environment, machines or a combination of the three occurring during the work process that is likely to cause injury, property damage and death or other undesirable events. Work accidents that occur always bring losses such as a decrease in the company's productivity because employees cannot work optimally, loss of manpower and of course reduce the company's profits. This research aims to analyze the order of priority for handling potential hazardous hazards that result in work accidents, analyze high-risk processes/activities that result in work accidents, and analyze control recommendations for potential hazards that have the risk of resulting in work accidents. The analysis method that will be used is the failure mode effect analysis (FMEA) method. The results of the study show that the potential danger of exposure to hot temperatures (melting process) has an RPN value of 297.7 so that the most risky production process is the process of forming or molding raw materials. The priority order of handling potential hazards from the glass bottle production process is exposure to hot temperatures, noise, exposure to glass bottle fragments, suffocation and being pinched by machines/conveyors. The controls that must be carried out are providing fans, providing insulation and shields, and providing drinking water so that the operator does not suffer from dehydration.